Zagrebelniy V.V. Increasing of high speed steels operational properties by combined laser-chemical-thermal treatment. - Загребельний, В.В. (Problems of Tribology, 2016)
The main objectives are: study of the effect of discrete processing circuit on the contact fatigue strength and wear resistance of steel P6M5; process design combined surface hardening tool with enhanced performance properties. In a paper ne investiqaled the influence of laser–aided surface harbening, patterns of descreete treatment followed by nitrating on wear resistance, contact fatigue and cutting cuttinq abilite of plates and drill bitts made of steel R6M5. Developed net-honeycomb pattern of treatment showed an increase of operational properties of cutting tools.Keywords: steel R6M5, discrete laser processing, net-honeycomb pattern of treatment, nitrating, durability.